Z is for Moose - Bingham, Kelly L., 1967- (Greenwillow Books, 2012)
Moose, terribly eager to play his part in the alphabet book his friend Zebra is putting together, then awfully disappointed when his letter passes, behaves rather badly until Zebra finds a spot for him.